Urbana ekonomija na globalnem jugu - Obeng-Odoom, Franklin (Urbani izziv, 2023)
Ukrainian Art Nouveau is considered in the context of the pan-European development of Art Nouveau in the architecture of the late nineteenth and early twentieth centuries. This stylistic direction is a demonstration of the self-identification of nations. It is hypothesized that the development of Ukrainian Art Nouveau in the architecture of Poltava at the beginning of the twentieth century expresses the identity of the place and national identification of the population, and is a reflection of national consciousness through architecture. This article defines and illustrates the special features of Ukrainian Art Nouveau as a manifestation of national character in the architecture of Poltava at the beginning of the twentieth century. The research was conducted using a cultural studies approach in the context of the general cultural development of the city. The general characteristics of the stylistic development of Poltava architecture at the beginning of the twentieth century are presented, and the place of Ukrainian Art Nouveau in the polystylism of the research period is revealed. The influence of Ukrainian Art Nouveau from the beginning of the twentieth century on the further development of Poltava architecture is analysed.
Keywords: cities; globalni jug; mesta; place identity; The Economist; the Global South; urban economics; urbana ekonomija